Evolving technologies for growing, imaging and analyzing 3D root system architecture of crop plants. Issue 3 (17th March 2016) - Piñeros, Miguel A.; Larson, Brandon G.; Shaff, Jon E.; Schneider, David J.; Falcão, Alexandre Xavier; Yuan, Lixing; Clark, Randy T.; Craft, Eric J.; Davis, Tyler W.; Pradier, Pierre‐Luc; Shaw, Nathanael M.; Assaranurak, Ithipong; et al.
Abstract: A plant's ability to maintain or improve its yield under limiting conditions, such as nutrient deficiency or drought, can be strongly influenced by root system architecture (RSA), the three‐dimensional distribution of the different root types in the soil. The ability to image, track and quantify these root system attributes in a dynamic fashion is a useful tool in assessing desirable genetic and physiological root traits. Recent advances in imaging technology and phenotyping software have resulted in substantive progress in describing and quantifying RSA. We have designed a hydroponic growth system which retains the three‐dimensional RSA of the plant root system, while allowing for aeration, solution replenishment and the imposition of nutrient treatments, as well as high‐quality imaging of the root system. The simplicity and flexibility of the system allows for modifications tailored to the RSA of different crop species and improved throughput. This paper details the recent improvements and innovations in our root growth and imaging system which allows for greater image sensitivity (detection of fine roots and other root details), higher efficiency, and a broad array of growing conditions for plants that more closely mimic those found under field conditions. Abstract : Variation in root system architecture (RSA) plays a major role in efficient nutrient acquisition under limiting conditions. Here we describe improvements in the growth and digital imaging of root systems that allow for imaging and analysis of RSA traits for a wide range of crop species under diverse treatment conditions.